2019
DOI: 10.2478/aucft-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Biosurfactant-Producing Lactic Acid Bacteria

Abstract: Biosurfactant attracts people’s attention because of its advantages of green and low toxicity. Lactic acid bacteria are beneficial to human and animal health. In order to make the application of surfactants safer, SDS standard curve was established, 65 strains of Lactic acid bacteria were used as screening source, and oil expanding circle was used as index to screen the strain with strong surfactant production capacity. The results showed that the standard curve of SDS was Y=34.82+(-1495.97) X1+33.11X2, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Also, they are considered 'generally regarded as safe (GRAS)' organisms and can be safely used in various applications such as food processing and health care (Hoque et al, 2010;Masci, 2013). Recently, attention has been directed towards biosurfactant production using various probiotic bacteria including LAB, due to their nonpathogenicity (Sharma et al, 2015;Dong et al, 2019). The biosurfactants produced by LAB exhibit antimicrobial as well as anti-adhesive activity to inhibit some pathogenic microorganisms (Gudina et al, 2010;Sambanthamoorthy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also, they are considered 'generally regarded as safe (GRAS)' organisms and can be safely used in various applications such as food processing and health care (Hoque et al, 2010;Masci, 2013). Recently, attention has been directed towards biosurfactant production using various probiotic bacteria including LAB, due to their nonpathogenicity (Sharma et al, 2015;Dong et al, 2019). The biosurfactants produced by LAB exhibit antimicrobial as well as anti-adhesive activity to inhibit some pathogenic microorganisms (Gudina et al, 2010;Sambanthamoorthy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These zones of growth inhibition were higher than 4.8 and 5.6 mm obtained by Yan et al (2019) with biosurfactants from Pediococcus acidilactici 27,167 and L. plantarum 27,172, respectively, at a concentration of 50 mg/mL. This observation suggests the good production ability of our isolates as there is a positive correlation between the diameters of the clear zone from the oil spreading test and the concentration of biosurfactants (Dong et al, 2019;Li et al, 2023). However, surface tension measurement should be performed as an additional method to strengthen the biosurfactant production ability of the isolates, as Mukherjee et al (2009) reported some limitations of the oil spreading test in detecting biosurfactants from certain microbial strains.…”
Section: Screening Of Be/bs Productionmentioning
confidence: 49%
“…They were the oil spreading test and the emulsifying activity. The oil spreading test, an indirect method that is more reliable in detecting low levels of biosurfactant production as determined by a tensiometer (Dong et al, 2019 ; Li et al, 2023 ; Yan et al, 2019 ), was used in this study to screen for the production of BE/BS by the isolates L. brevis S4 and L. plantarum S5. The two isolates showed positive results in the oil spreading test, with zones of growth inhibition of 26 and 30 mm for L. brevis S4 and L. plantarum S5, respectively (Figure 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…Chemical surfactant type amino acid surfactant is also existing, related research is more, but amino acid production of lactic acid bacteria on surfactant study is less (Zhang et al, 2016;Fisseha et al, 2015). In a previous work, the above liquid and the surface activity of the cell surface were used as indicators to screen out lactobacillus F70 from 69 strains of lactobacillus as the target bacteria for producing surface active substances, which were identified as Pediococcus acidilactici F70 by 16S rDNA (Dong et al, 2019). On the basis of these studies, the purpose of this study is to further screen 19 amino acids by Plackett Burman design to optimize the composition of the culture medium, so as to obtain higher surface activity through Pediococcus acidilactici F70 fermentation, providing a new idea for the production of surfactant by microorganisms.…”
Section: Introductionmentioning
confidence: 99%